Energy Economical and Environmental Analysis of Industrial Boilers Using Fuel Switching - Atabani, A.E.; Rahman, S.; Silitonga, A.S.; Sebayang, A.H. (International Journal on Advanced Science, Engineering and Information Technology, 2011)
The successful implementation of the industrialization plan in Malaysia in 1985 has led to change this country from an agricultural economy into industrial based economy. The industrial sector represents the highest consuming sector across all other sectors and accounts for about 48 of all total energy demand. This study is concerned with an energy saving, economic and environmental analysis of industrial boilers in Malaysian paper and pulp industries when applying the concept of fuel switching. It has been found that 11,946 ton of CO2 and RM 1,872,532 could be saved annually, when switching between diesel fuel and biomass by a percentage of 50 for both instead of using 100 of diesel fuel. Also it has been found that 7,495,640 kg of CO2 and RM 923,431 could be saved annually, when switching between diesel fuel and natural gas by a percentage of 50 for both instead of using 100 of diesel fuel. All these results represent high energy saving, environmental and economic benefits for a small developing country like Malaysia.